A new species of the Simulium (Simulium) variegatum species-group (Diptera: Simuliidae) from Thailand - Hiroyuki Takaoka (2019)
© 2019 Elsevier B.V. A new species of black fly, Simulium (Simulium) luculentum, is described from specimens collected in Thailand, and is assigned to the Simulium variegatum species-group of the subgenus Simulium Latreille. This new species is distinguished from most members of this species group in the female by the mid femur and tibia entirely yellowish; and in the pupa by the gill with six filaments, which are somewhat inflated basally. This species represents the fifth member of the S. variegatum species-group recorded from Thailand.